Change of peroxidase enzyme activities in annual cuttings during rooting - Fekete, Szabolcs; Mándy, Andrea; Stefanovits-Bányai, Éva (Acta Biologica Szegediensis, 2002)
The peroxidase enzyme (POD) activities (U/mg protein) were measured by spectrophotometric method in different organs of some annual ornamental plant cuttings during rooting period. The examined species were Lantana camara L. "Schneewittchen", Lantana camara L "Prof. Raoux", Heliotropium arborescens L. an d Helichrysum stoechas (L.) Moench. Rooting of cuttings was more than 90% at all species. The POD enzyme activities increased from the top towards the base of cuttings at all species and in all measuring dates. The highest POD activities were in the base measured one week after cutting, these values decreased in connection with the root formation in all cases. In the case of Helichrysum stoechas the rooting took much longer time while it was shown in the ten times lower POD enzyme activities in all measuring dates.